Seed Borne Mycoflora of Tribal Saved Hill Rice, Oryza sativa in Mizoram, Northeastern of India - Singh, A Ratankumar; Boopathi, T; Singh, S B; Dutta, S K; Singh, L Sanajoaba; Lungmuana, Lungmuana; Saha, Saurav; Singh, N Hemanta (Indian Journal of Hill Farming, 2019)
Detection of seed borne pathogens through seed health testing is a critical step in the management of diseases for healthy crop establishment. The tribal farmers of Northeastern India saved their own rice seed which remains poor quality and act as carrier of many mycoflora that hinder seed viability and crop stand. This study was carried out to assess seeds of tribal farmers’ saved hill rice (twenty landraces) and improved varieties (four improved varieties) for their seed borne mycoflora collected from Mizoram, Northeastern India. The seeds were subjected to blotter, agar plate techniques and paper towel method to identify various seed borne mycoflora and their germination per cent, seed vigour index, respectively. A total of 21 fungi were recorded like Acremoniella sp. Alternaria tenuis, Curvularia lunata, C. oryzae, Dreschslera oryzae, Fusarium moniliforme, F. oxysporum, F. semitectum, Microdochium oryzae , Pyricularia grisea, Rhizoctonia sp,. Saracladium oryzae, Tilletia sp., Trichothesiums sp., Stilaginoidea virens, Aspergillus flavus, A. niger, Penicillium sp. and Rizopus stolonifer and among these pathogen, Fusarium moniliforme was pre dominant in all tested rice samples ranging from (15-35%) and (54-82.0%) of agar plate and blotter paper method, respectively. Maipum (1317.43) and Manipur Nem (1171.76) showed the better performance in terms of seed germination and seedling vigour index. Idaw, recorded the maximum number of pathogen genera (14), least germination (45.45%) and vigour index (37.42). Tribal famers’ saved hill rice seeds are found to be more associated with seed borne mycoflora than the improved varieties.